The Transcription Factor EB (TFEB) sensitizes the heart to chronic pressure overload - Wundersitz, Sebastian; Pablo Tortola, Cristina; Schmidt, Sibylle; Oliveira Vidal, Ramon; Kny, Melanie; Hahn, Alexander; Zanders, Lukas; Katus, Hugo; Sauer, Sascha; Butter, Christian; Luft, Friedrich C.; Müller, Oliver J.; et al. (International journal of molecular sciences, 2022)
The transcription factor EB (TFEB) promotes protein degradation by the autophagy and lysosomal pathway (ALP) and overexpression of TFEB was suggested for the treatment of ALP-related diseases that often affect the heart. However, TFEB-mediated ALP induction may perturb cardiac stress response. We used adeno-associated viral vectors type 9 (AAV9) to overexpress TFEB (AAV9-Tfeb) or Luciferase-control (AAV9-Luc) in cardiomyocytes of 12-week-old male mice. Mice were subjected to transverse aortic constriction (TAC, 27G; AAV9-Luc: n = 9; AAV9-Tfeb: n = 14) or sham (AAV9-Luc: n = 9; AAV9-Tfeb: n = 9) surgery for 28 days. Heart morphology, echocardiography, gene expression, and protein levels were monitored. AAV9-Tfeb had no effect on cardiac structure and function in sham animals. TAC resulted in compensated left ventricular hypertrophy in AAV9-Luc mice. AAV9-Tfeb TAC mice showed a reduced LV ejection fraction and increased left ventricular diameters. Morphological, histological, and real-time PCR analyses showed increased heart weights, exaggerated fibrosis, and higher expression of stress markers and remodeling genes in AAV9-Tfeb TAC compared to AAV9-Luc TAC. RNA-sequencing, real-time PCR and Western Blot revealed a stronger ALP activation in the hearts of AAV9-Tfeb TAC mice. Cardiomyocyte-specific TFEB-overexpression promoted ALP gene expression during TAC, which was associated with heart failure. Treatment of ALP-related diseases by overexpression of TFEB warrants careful consideration.